Changing the diagnostic paradigm for sugarcane: development of a mill-based diagnostic for ratoon stunting disease in crude cane juice - Burman, Sriti; Mason, Michael G.; Hintzsche, Jessica; Zou, Yiping; Gibbs, Lucy; MacGillycuddy, Laura; Magarey, Robert C.; Botella, José R. (Frontiers in Plant Science, 2023)
The availability of efficient diagnostic methods is crucial to monitor the incidence of crop diseases and implement effective management strategies. One of the most important elements in diagnostics, especially in large acreage crops, is the sampling strategy as hundreds of thousands of individual plants can grow in a single farm, making it difficult to assess disease incidence in field surveys. This problem is compounded when there are no external disease symptoms, as in the case for the ratoon stunting disease (RSD) in sugarcane. We have developed an alternative approach of disease surveillance by using the crude cane juice expressed at the sugar factory (mill). For this purpose, we optimized DNA extraction and amplification conditions for the bacterium Leifsonia xyli subsp xyli, the causal agent of RSD. The use of nucleic acid dipsticks and LAMP isothermal amplification allows to perform the assays at the mills, even in the absence of molecular biology laboratories. Our method has been validated using the qPCR industry standard and shows higher sensitivity. This approach circumvents sampling limitations, providing RSD incidence evaluation on commercial crops and facilitating disease mapping across growing regions. There is also potential is to extend the technology to other sugarcane diseases as well as other processed crops.